Next-generation sequencing yields the complete chloroplast genome of Abies fanjingshanensis, an Endangered species from South China - Zhen-Ni Guo; Xiao-Fang Lu; Ya-bin Dong; Chang-Jing Wu; Guo-Yin Li (Mitochondrial DNA. Part B. Resources, 2019)
Abies fansipanensis is an Endangered species in South China with less than 2500 mature trees. In this study, we reported the complete chloroplast genome of A. fansipanensis. The complete chloroplast genome is 120,057 bp in length, comprising a large single copy (LSC) region of 65,355 bp, a small single copy (SSC) region of 54,174 bp, and two inverted repeat regions (IRa and IRb) of 264 bp each. The genome contains 114 genes and there were 68 peptide-encoding genes, 35 tRNA genes, four rRNA genes, 6 open reading frames, and 1 pseudogene. Loss of ndh genes and inverted repeat sequences were identified in this genome. The phylogenetic analysis confirms that the Abies species are supported as monophyletic, with high bootstrap values.